Processing Suitability of Physical Modified Non-GMO High-Amylose Wheat Flour as a Resistant Starch Ingredient in Cookies - Yujin Moon; Meera Kweon (Molecules)
High-amylose wheat (HAW), developed through non-genetic modification, addresses the growing demand for clean-label and nutritionally enhanced food products. This study systematically investigated the effects of heat-moisture treatment (HMT; 20% and 25% moisture levels) on the physicochemical properties and cookie-making performance of HAW flour (HAWF) and soft wheat flour (SWF). HMT promoted moisture-induced agglomeration, leading to increased particle size, reduced damaged starch content, and enhanced water and sucrose solvent retention capacities. Although the amylose content remained largely unchanged, pasting behavior was differentially affected, with increased viscosities in SWF and slight decreases in HAWF. Thermal analyses demonstrated elevated gelatinization temperatures, indicating improved thermal stability, while X-ray diffraction revealed alterations in starch crystallinity. Furthermore, HMT weakened gluten strength and modified dough rheology, effects more pronounced in HAWF. Cookies prepared from HMT-treated flours exhibited larger diameters, greater spread ratios, and reduced heights. In vitro digestibility assays showed a marked reduction in rapidly digestible starch and increases in slowly digestible and resistant starch fractions, particularly in HAWF cookies. Collectively, these findings establish HMT as an effective strategy for modulating flour functionality and enhancing cookie quality, while concurrently improving the nutritional profile through the alteration of starch digestibility characteristics.